Designing mobilities - Jensen, Ole B. 1965- (Aalborg University Press, 2014)
How is the width of the pavement shaping the urban experience? How is the material design of transport infrastructure and mobile technology affording social interaction in everyday life spaces? How are people inhabiting these spaces with their bodies and in accordance to social and cultural norms? These are some of the questions that this book raises in order to explore how the design of mobile sites and situations affect people's everyday life. The book takes point of departure in the author's book 'Staging Mobilities' (Routledge, 2013) in which it is argued that mobility is much more than simple movements of people, goods, and information 'from A to B'. Accordingly, the way people, goods, and information moves shapes the way we understand our built environment, other consociates, and ourselves. The book contributes with a new and critical-creative gaze on what might seem to be trivial and mundane acts of moving in the city. 'Designing Mobilities' is based on more than a decade of academic research by Professor of Urban Theory, Ole B. Jensen and a must-read for students and scholars with an interest in urban studies, urban design, architecture, urban planning, transport planning and geography, urban geography, anthropology, design studies, interaction design, and urban sociology
Keywords: Design; By og rum; Byplanlægning; Bysociologi; Stadtplanung